An Orientation Map for Motion Boundaries in Macaque V2. (26th September 2014) - Chen, Ming; Li, Peichao; Zhu, Shude; Han, Chao; Xu, Haoran; Fang, Yang; Hu, Jiaming; Roe, Anna W.; Lu, Haidong D.
Abstract: The ability to extract the shape of moving objects is fundamental to visual perception. However, where such computations are processed in the visual system is unknown. To address this question, we used intrinsic signal optical imaging in awake monkeys to examine cortical response to perceptual contours defined by motion contrast (motion boundaries, MBs). We found that MB stimuli elicit a robust orientation response in area V2. Orientation maps derived from subtraction of orthogonal MB stimuli aligned well with the orientation maps obtained with luminance gratings (LGs). In contrast, area V1 responded well to LGs, but exhibited a much weaker orientation response to MBs. We further show that V2 direction domains respond to motion contrast, which is required in the detection of MB in V2. These results suggest that V2 represents MB information, an important prerequisite for shape recognition and figure-ground segregation.